Inclusive landscape management plan for the transformation of agrifood systems in the Doma-Rutu socio-ecological landscape, Nigeria - Igbadun, H. E.; Ojeleye, Oluwaseun Adebayo; Oke, Adebayo; Atampugre, Gerald; Tilahun, Seifu A.; Ismail, H.; Jonathan, J.; Cofie, Olufunke O. (International Water Management Institute (IWMI). CGIAR Initiative on West and Central African Food Systems Transformation, 2024)
The Doma-Rutu socio-ecological landscape in Nasarawa State, Nigeria, faces several socio-ecological challenges such as deforestation, water pollution, and unsustainable land-use practices. To address these issues, the International Water Management Institute (IWMI) under the CGIAR Initiative on West and Central Africa AgriFood Systems Transformation (TAFS-WCA) has facilitated the co-development of a comprehensive Inclusive Landscape Management Plan (ILMP). The ILMP is a collaborative effort involving contributions from stakeholders such as the government, local communities, marginalized groups, NGOs, and research institutions.